2015
DOI: 10.1111/ceo.12480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amniotic membrane extract on primary human corneal epithelial and limbal cells

Abstract: HCE cells treated with AMX healed faster after mechanical insult, suggesting a potential benefit in acute corneal injuries. Under oxidative stress, human limbal cells, a more proliferative cell type, showed superior viability compared with HCE cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 18 publications
(35 reference statements)
1
32
0
Order By: Relevance
“…Liang et al demonstrated the benefits of AME for ocular chemical burns with a preliminary study demonstrating its ability to reduce corneal inflammation and promote re-epithelization (65) . Dudok et al used AME to treat corneal and limbal epithelial cells under mechanical stress, which healed faster (66) . Collectively, these results suggests the potential benefit of AME for the treatment of acute corneal injuries.…”
Section: Therapeutic Use Of Gf/cytokines In Ocular Surface Diseasesmentioning
confidence: 99%
“…Liang et al demonstrated the benefits of AME for ocular chemical burns with a preliminary study demonstrating its ability to reduce corneal inflammation and promote re-epithelization (65) . Dudok et al used AME to treat corneal and limbal epithelial cells under mechanical stress, which healed faster (66) . Collectively, these results suggests the potential benefit of AME for the treatment of acute corneal injuries.…”
Section: Therapeutic Use Of Gf/cytokines In Ocular Surface Diseasesmentioning
confidence: 99%
“…Most of the beneficial effects of AM are attributed to biomolecules, such as fibronectin, hepatocyte growth factor (HGF), epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), transforming growth factor (TGF), and collagen types I, III, IV, and V, which are potent sources for corneal regeneration. 18 They combine to facilitate migration, adhesion, and differentiation of the corneal epithelium, while preventing apoptosis. AM downregulates the expression of such cell surface markers as CD80, CD86, and major histocompatibility complex class 2 antigen, which are modulators of the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…AME contains many of the similar properties of cryopreserved AM. 18 Similar to AM, it has high levels of a myriad of growth factors, including EGF, HGF, bFGF, protease inhibitors, and a novel matrix component known as heavy chain-hyaluronan pentraxin 3 (HC-HA/PTX3), which acts to prevent inflammation, angiogenesis, and scarring. 17 , 22 AME retains anti-inflammatory activities and often acts through downregulating and inducing apoptosis in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…The article presented in this issue by Dudok et al . provides insights into the mode of action of AMX.…”
mentioning
confidence: 99%
“…This humoral approach is exemplified by the use of amniotic membrane extract (AMX), as pioneered by Tseng's group, 18,19 and demonstrated to be effective both in the laboratory 20,21 and in clinical trials. 22,23 The article presented in this issue by Dudok et al 2 provides insights into the mode of action of AMX. The authors used in vitro wounding models of corneal epithelial cell lines in the laboratory.…”
mentioning
confidence: 99%